5-H-1, 2-Oxaphosphole 2-oxides, key building blocks for diversity oriented chemical libraries. Issue 49 (8th December 2016) - Fourgeaud, Pierre; Volle, Jean-Noël; Vors, Jean-Pierre; Békro, Yves-Alain; Pirat, Jean-Luc; Virieux, David
Abstract: A simple and effective preparation of 2-hydrogeno-5 H -1, 2-oxaphosphole 2-oxides9a–b has been developed involving direct cyclization of H -phosphinic allenes. H -1, 2-Oxaphospholenes9a–b showed to be excellent building blocks for diversity oriented small chemical libraries. Then, reactivity of the cyclic H -phosphinates9a–b was investigated through Pd(0) catalyzed arylation, Pudovik and three-component Kabachnik–Fields reactions. 5 H -1, 2-Oxaphospholes are excellent heterocyclic platforms offering different opportunities to modulate the substituent directly bounded to the phosphorus atom. Graphical abstract: